2020
DOI: 10.1016/j.soncn.2020.151049
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Unmet Need and Access to Supportive Care for Men Receiving Androgen Deprivation Therapy for Prostate Cancer: A Bi-national Study

Abstract: Objective: Men affected by incurable prostate cancer is expected to increase worldwide. Research is needed to enable men to share their experiences of unmet supportive care needs in current care delivery. We aimed to identify the most frequently reported domains of unmet supportive care needs, levels of anxiety, depression, distress, health-related quality of life, and to identify any perceived barriers to receiving supportive care.Data Sources: Men diagnosed with prostate cancer who had received a minimum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
3
9
0
2
Order By: Relevance
“…However, some men experienced anxiety and fear about: their own mortality, the cancer spreading, the future, and the results of treatments. These findings are consistent with previous studies that found that 54% of PC survivors living with advanced disease manifest uncertainty, anxiety, or regret about treatment decisions (Paterson et al, 2020;Ralph et al, 2020). More research is needed to determine which SC interventions may contribute to a better psychological burden control (Kuon et al, 2019;O'Shaughnessy et al,2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, some men experienced anxiety and fear about: their own mortality, the cancer spreading, the future, and the results of treatments. These findings are consistent with previous studies that found that 54% of PC survivors living with advanced disease manifest uncertainty, anxiety, or regret about treatment decisions (Paterson et al, 2020;Ralph et al, 2020). More research is needed to determine which SC interventions may contribute to a better psychological burden control (Kuon et al, 2019;O'Shaughnessy et al,2015).…”
Section: Discussionsupporting
confidence: 89%
“…On the surface, the convergent findings regarding physical and emotional unmet needs appear to be consistent with the extant literature suggesting that advanced PC therapies are associated with fatigue, pain, decreased libido, impotence, anxiety, and existential concerns (Chambers et al, 2019;Holm et al, 2018;Steentjes et al, 2018;Paterson et al, 2015;Bermat et al, 2016). However, these high rates may be clinically relevant because, despite the impact of these unmet SC needs and the current guidelines, the SC beyond routine clinical care appears to be suboptimal at best (Handberg et al, 2018;Lo & Buss, 2019;Nekhlyudov et al, 2017;Paterson et al, 2020).…”
Section: Discussionsupporting
confidence: 69%
“…Our study also showed coordination gaps between healthcare services and cancer organizations despite their supplementary role and importance for men with PCa. Our findings, like those of Ettridge et al (2018) suggest that not all men know about supportive care services because information about them is fragmented and not due to reduced accessibility as described by other studies (Chambers et al, 2018;Paterson et al, 2020). Moreover, our findings show that urologists and GPs may not refer men with PCa to these services due to misunderstandings over the content of the services offered, particularly the belief that they focus only on disease.…”
Section: Coordination Gaps With Multiple Explanatory Factors Are Commonsupporting
confidence: 46%
“…Cependant, certains hommes indiquent avoir éprouvé de l'anxiété et de la peur concernant leur mort, la propagation du cancer, leur avenir en général et les résultats des traitements. Ces résultats sont conformes à ceux d'études antérieures ayant révélé que 54 % des survivants du cancer de la prostate à un stade avancé manifestent de l'incertitude, de l'anxiété ou des regrets relativement à leurs décisions de traitement (Paterson et al, 2020;Ralph et al, 2020). Des recherches supplémentaires sont nécessaires pour déterminer quels types de soins de soutien seraient les plus utiles pour gérer le fardeau psychologique (Kuon et al, 2019;O'Shaughnessy et al, 2015).…”
Section: Discussionunclassified
“…À première vue, les résultats convergents concernant les besoins non satisfaits d'ordre physique et émotionnel semblent correspondre à la littérature existante qui suggère que les traitements avancés du cancer de la prostate engendrent de la fatigue, de la douleur, une baisse de la libido, de l'impuissance, de l'anxiété et des préoccupations existentielles (Chambers et al, 2019;Holm et al, 2018;Steentjes et al, 2018;Paterson et al, 2015;Bermat et al, 2016). Cependant, ces résultats élevés peuvent être cliniquement pertinents, car, malgré l'importance de ces besoins non satisfaits en matière de soins de soutien et les directives actuelles, les soins de soutien dépassant le cadre des soins cliniques de routine semblent loin d'être optimaux (Handberg et al, 2018;Lo et Buss, 2019;Nekhlyudov et al, 2017;Paterson et al, 2020).…”
Section: Discussionunclassified